2019
DOI: 10.1007/s42452-019-1240-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of magnesium–iron layered double hydroxide and application to nitrate removal

Abstract: Nitrate is an important ion in agriculture and industry although it is known to cause eutrophication and affect human health. Removal of nitrogen by physicochemical treatment such as sedimentation and membrane separation remains difficult. The selectivity of commercial adsorbents for nitrate is among the lowest for anions, because the selectivity of an adsorbent as an ion exchange resin is based on the valence of the ion. Layered double hydroxide acts as an anion adsorbent, and the target anion adsorbs in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Meanwhile, other studies indicate that LDH is dissolved if the pH is stabilized by the addition of acid or base during the adsorption experiment (Hongo et al, 2008;Luengo et al, 2017;Zhou et al, 2011). And the phosphate adsorption efficacy with competitive anions were reported by Kamimoto et al, phosphate ions have higher affinity to MgFe-LDH compare nitrate (NO3 -), chloride (Cl -) and sulfate (SO4 -) (Kamimoto et al, 2019). Also, Drenkova-Tuhtan et al, reported MgFe-LDH@magnetic particles shows similar phosphate adsorption efficacy compare to carbonate ions (CO3 2-) (Drenkova-Tuhtan et al, 2013).…”
Section: Introductionmentioning
confidence: 84%
“…Meanwhile, other studies indicate that LDH is dissolved if the pH is stabilized by the addition of acid or base during the adsorption experiment (Hongo et al, 2008;Luengo et al, 2017;Zhou et al, 2011). And the phosphate adsorption efficacy with competitive anions were reported by Kamimoto et al, phosphate ions have higher affinity to MgFe-LDH compare nitrate (NO3 -), chloride (Cl -) and sulfate (SO4 -) (Kamimoto et al, 2019). Also, Drenkova-Tuhtan et al, reported MgFe-LDH@magnetic particles shows similar phosphate adsorption efficacy compare to carbonate ions (CO3 2-) (Drenkova-Tuhtan et al, 2013).…”
Section: Introductionmentioning
confidence: 84%
“…Thus, the adopted model for the next assays was as follows. ORP = a + b pH + c log 10 NO − 3 (6) This adopted model refers to using a synthetic medium; however, in real effluents, the conditions are more complex and stressful for bacteria. Nevertheless, this proposed model can be applied in real effluents where electroactive species exchange electrons in an equilibrium state.…”
Section: Modeling and Monitoring Using Orpmentioning
confidence: 99%
“…On the one hand, physicochemical methods such as sedimentation and membrane separation [5] have been shown to be ineffective in completely removing nitrates [6]. On the other hand, electrocoagulation [7], heterogeneous catalysis, electrochemical [8] and bioelectrochemical [9] methods were sufficiently efficient at laboratory scales.…”
Section: Introductionmentioning
confidence: 99%
“…Ronghua Li et al [27] developed Mg/Al-layered double hydroxide at different mole ratios and revealed improved phosphate adsorption with increasing Mg/Al ratio in the Mg/Al-LDHs biochar composites capacity. Yuki Kamimoto et al [28] concluded excellent adsorption performance of nitrate onto magnetic calcined Mg-Fe LDH. Muayad Al Jaberi et al [29] prepared CaFe-layered double hydroxide by co-simple co-precipitation technique and reported a maximum removal capacity of 130 mg/g.…”
Section: Introductionmentioning
confidence: 99%